The element of research skills for the implementation of research by postgraduate students in Malaysia - Sumarwati, Sri; Amiruddin, Mohd Hasril; Madar, Ahmad Rizal (2021)
Postgraduate research is more demanding of the ability of students to be independent, where throughout the process conducting research it is a challenging journey. This study was conducted to know the expert opinion about the research skills for postgraduate students in Malaysia. This study uses the Fuzzy Delphi Method to identify expert agreement about the elements of research skills. The total sample is 13 experts in the social sciences and humanities were selected using purposive sampling. Data were analysed based on the calculation of the Fuzzy set. This study found that the element of research skills are inference skills, research design skills, moral and ethical research skills, and integrity skills. The implementation of research skills for conducting research is expected to provide opportunities for students to increase the potential and personal qualities during their studies at the postgraduate level.